OVERVIEW OF OUTPATIENT CANCER REHABILITATION PROVIDED BY DESIGNATED CANCER HOSPITALS IN JAPAN: A SURVEY RESEARCH - Takuya Fukushima; Tetsuya Tsuji; Jiro Nakano; Shun Ishii; Shinsuke Sugihara; Hiroshi Sato; Juichi Kawakami; Hitoshi Kagaya; Akira Tanuma; Ryuichi Sekine; Keita Mori; Sadamoto Zenda; et al. (Journal of Cancer Rehabilitation, 2023)
Background This study aimed to clarify the details of outpatient cancer rehabilitation provided by designated cancer hospitals in Japan. Materials and Methods Questionnaires were sent to 427 designated cancer hospitals in Japan. We surveyed whether outpatient rehabilitation was provided, including detailed content, such as intervention time and frequency, Dietz classification, cancer type, and intervention content. Results Responses were obtained from 235 (55.0%) surveyed facilities, of which 92 (39.1%) facilities provided outpatient cancer rehabilitation. Outpatient cancer rehabilitation was mainly provided for 20–40 minutes per session, 1–2 times per week, for the Dietz classification of restorative, supportive, and preventive phases. Breast cancer was the most common cancer type, followed by lung, colorectal, and stomach. The implementation rate of head and neck cancer and bone and soft tissue sarcoma was significantly higher at university hospitals and cancer centers than at general hospitals (P < 0.01). Resistance training was the most common intervention, followed by range of motion exercise, pulmonary rehabilitation, and support for lymphedema; and the frequency of pulmonary rehabilitation was significantly higher in general hospitals than in university hospitals (P < 0.05). Conclusions Outpatient cancer rehabilitation in Japan is less prevalent than that in inpatient settings. Many facilities provide interventions for shoulder joint dysfunction and lymphedema after breast cancer surgery, as well as prehabilitation and postoperative recovery for lung and gastrointestinal cancer. It is expected that rehabilitation tailored to each facility’s characteristics and verification of its effectiveness will contribute to its diffusion and development.